Adverse Childhood Experiences and Higher-Level Functional Limitations Among Older Japanese People: Results From the JAGES Study. (2nd June 2017) - Amemiya, Airi; Fujiwara, Takeo; Murayama, Hiroshi; Tani, Yukako; Kondo, Katsunori
Abstract: Background: A life-course perspective is essential in understanding the determinants of higher-level functional limitations. We examine the impact of adverse childhood experiences (ACEs) on higher-level functional limitations in older people. Methods: Data were from the Japan Gerontological Evaluation Study 2013, a population-based cohort of independent people aged 65 years or older across Japan ( n = 19, 220). ACEs before the age of 18 were assessed in terms of seven adversities: parental death, parental divorce, parental mental illness, family violence, physical abuse, psychological neglect, and psychological abuse. Associations between the cumulative number of ACEs and higher-level functional limitations were investigated by multivariate Poisson regression with robust error variances, adjusted for age, gender, childhood disadvantage, adult sociodemographics, adult health behaviors, and health status. Results: Of the older people, 36.3% reported at least one ACE. Older people who had experienced two or more ACEs showed significantly greater higher-level functional limitations than those with no ACE in a crude model (prevalence ratio, PR = 1.61, 95% confidence interval, CI = 1.51–1.71). After adjusting the covariates, this association remained (PR = 1.19, 95% CI = 1.12–1.27). Conclusions: ACEs showed robust independent effects on higher-level functional limitations among older Japanese without disabilities, even after adjusting for potential covariates in childhood and adulthood. The current findings may help in understanding the impact of the latent effects of ACEs on functional limitations in older people.